Design and fabrication of tubular dielectric elastomer actuator - Tan, Desmond Di Teng (2014)
Dielectric elastomer actuators (DEAs) are soft capacitors that undergo large shape changes when electrically activated. In its most basic planar form, the DEA expands in area as it decreases in thickness. When a planar DEA is rolled up, deformations are limited to just the axial direction; the linear strokes of rolled DEAs has been said to be able to mimic the motion of natural muscles. In order to use rolled DEAs as artificial muscles, they should be able to generate large strokes and forces, wherein generated force is related to its breakdown field strength. However, in literature, rolled DEAs generally have poor performances in terms of strain (maximum of 37%) and breakdown strength (maximum of 164 MV/m). The objective of this project is to improve the strain and breakdown strength performance of core-free tubular DEAs, which are rolled DEAs that have no core and only a single layer of active DEA. As such, the first part of this report is focused on the improvement of actuated strain, by studying the use of pre- stretch, while the second part of this report is focused on the improvement of breakdown field strength, via the use of dielectric liquids to prevent electrical breakdowns. Pre-stretch, which is a mechanical stretch applied to the DEA prior to electrical activation, is commonly used to enhance actuated strains in planar DEAs. The effect of pre-stretch on the strain performance of tubular DEAs was studied in the first part of this report. By fabricating and testing tubular DEAs with fourteen different combinations pre-stretches in the axial and circumferential directions, it was found that varying the magnitude and ratio of the pre-stretches resulted in different strain performances. The maximum strain obtained was 80%, which is more than double the maximum reported strain for a rolled DEA. It was also observed that at pre-stretches that were too high, the DEAs tended to break down prematurely due to necking. Conversely, at pre-stretches that were too low, the strain-enhancement benefit of pre- stretching was not fully utilised. In addition, it was confirmed that pre-stretch should be higher in the circumferential direction than in the axial direction in order to attain better strain performance. The optimum pre-stretch for tubular DEAs was also observed to be different from that for planar DEAs.Dielectric liquid immersion is a method that has been used to improve the breakdown strengths of planar DEAs. This involves the use of a dielectric liquid to transfer heat away from the DEA during electrical shorting, thereby circumventing electrical breakdown; consequently, this increases the DEA’s breakdown field strength. This method has never been used for rolled DEAs and was therefore its application to tubular DEAs was studied in the second part of this report. Instead of immersing the entire tubular DEA in the dielectric liquid, which would be impractical, a novel design was used to encapsulate the dielectric liquid between the active DEA layer and a passive membrane. Doing so enabled high breakdown field strengths in tubular DEAs, of up to 712 MV/m, which is about 50% more than that of similar tubular DEAs without dielectric liquid encapsulation. This enhanced breakdown field strength can be attributed to self-clearing and the prevention of thermal runaway by the dielectric liquid. However, strain performance was sacrificed: a 55% strain was obtained by tubular DEAs with dielectric liquid encapsulation, while an 80% strain was obtained by tubular DEAs without dielectric liquid encapsulation. This reduction in actuated strain was caused by the added stiffness of the passive encapsulating membrane layer. This work has shown that the actuated strain and breakdown field strength of tubular DEAs can be improved via the optimisation of pre-stretch and dielectric liquid encapsulation, respectively. By using a pre-stretch of 6 and 4 in the circumferential and axial directions, respectively, tubular DEAs could attain a maximum strain of 80% and breakdown strength of 475 MV/m. Alternatively, by using the same pre-stretch configuration coupled with dielectric liquid encapsulation, tubular DEAs could attain a maximum strain of 55% and breakdown strength of 712 MV/m. Either of these two configurations of tubular DEAs is an improvement over the prevailing record for maximum strain (37%) and breakdown strength (164 MV/m) of rolled DEAs.